Causes and Pattern of Non Compliance with Instructions given after Fitting of Removable Partial Dentures (RPDs) among Patients in a Nigerian Teaching Hospital - T.J. Ogunrinde (Nigerian Dental Journal)
Objective: The study was carried out to assess the pattern of non compliance with instructions given after fitting of RPDs and to evaluate the reasons for non compliance. Patients and method: The study was a cross-sectional study among consecutive denture wearers in a Nigerian teaching Hospital. An interviewer administered questionnaire was used to assess the pattern and causes of noncompliance with post denture insertion instructions. Data collected were imputed into a personal computer and analyzed using SPSS version 16. Chisquare was used to test association between categorical variables. The level of significance was set at p<0.05. Results: Two hundred and thirty two patients, participated in the study. One hundred and twenty nine patients did not comply with brushing the denture with brush and soft soap. The proportion of males (56.9%) and patients above 40 years (61. 0%) that did not comply was greater than the proportion of females (54.3%) and patients 40 years and below (41.2%) respectively. There was a statistically significant relationship between the age of the patient and non compliance with cleaning the denture with soft soap. One hundred and ninety four patients did not comply with twice annual routine visit to dentist. The proportion of males (84.5%) and patients above 40 years (84.1%) that did not comply was greater than the proportion of females (82.8%) and patients 40 years and below (82.4%) respectively. The reasons for non compliance with cleaning denture with brush and soft soap included; more convenience (4.3%), detest the taste of soap (5.6%), while the reasons for non compliance with routine visit to dentist included no time (15.1%), financial problem (12.1%), and "I see no need for it when there was no dental problem" (44.0%). Conclusion: Non compliance is more common among male patients and patients above forty years. Dentists should lay more emphasis on post denture insertion instructions especially for male patients.